2006
DOI: 10.1161/01.str.0000242775.14642.b8
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy Applied Transcranially to Rats After Induction of Stroke Significantly Reduces Long-Term Neurological Deficits

Abstract: Background and Purpose-Low-level laser therapy (LLLT) modulates various biological processes. In the present study,we assessed the hypothesis that LLLT after induction of stroke may have a beneficial effect on ischemic brain tissue. Methods-Two sets of experiments were performed. Stroke was induced in rats by (1) permanent occlusion of the middle cerebral artery through a craniotomy or (2) insertion of a filament. After induction of stroke, a battery of neurological and functional tests (neurological score, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(211 citation statements)
references
References 20 publications
4
205
0
2
Order By: Relevance
“…23 This effect was partially attributed to a significant increase in the number of intact mitochondria and ATP content, as well as to antioxidative enzyme activity in LELI induced hearts of rats and dogs as compared with non-irradiated hearts. LELI applied transcranially six hours postembolic stroke in rabbits and 24 hours postischemic stroke in rats caused a significant improvement in the neurological score over sham-operated experimental animals, 24 a finding that has been confirmed by others. 25 It is thought that LELI causes suppression of nitric oxide synthase activity and upregulation of TGF-β1, which are considered neurotoxic and neuroprotective, respectively.…”
Section: Low-energy Laser Irradiationsupporting
confidence: 71%
“…23 This effect was partially attributed to a significant increase in the number of intact mitochondria and ATP content, as well as to antioxidative enzyme activity in LELI induced hearts of rats and dogs as compared with non-irradiated hearts. LELI applied transcranially six hours postembolic stroke in rabbits and 24 hours postischemic stroke in rats caused a significant improvement in the neurological score over sham-operated experimental animals, 24 a finding that has been confirmed by others. 25 It is thought that LELI causes suppression of nitric oxide synthase activity and upregulation of TGF-β1, which are considered neurotoxic and neuroprotective, respectively.…”
Section: Low-energy Laser Irradiationsupporting
confidence: 71%
“…839 The postulated mechanism of action is photobiostimulation, with near-infrared radiation absorbed by mitochondrial chromophores, which accelerates enzymatic activity, increases adenosine triphosphate production, and promotes tissue preservation in the ischemic penumbra and enhanced neurorecovery. [840][841][842] Evidence of benefit in animal models [843][844][845][846] led to a safety and preliminary efficacy trial in 120 patients with acute ischemic stroke, which demonstrated statistically better outcomes in the treated patients as measured by the NIHSS, mRS, Barthel index, and Glasgow Outcome Scale. 847 A confirmatory trial enrolling 660 patients reported a positive trend but not a definitive benefit, and an additional pivotal trial using refined selection criteria is planned.…”
Section: Near-infrared Laser Therapymentioning
confidence: 99%
“…26 Finally, several groups have suggested that NIr promotes functional recovery by stimulating neurogenesis and neuronal migration. 8,19,29 It remains to be determined which of these mechanisms protects SNc cells, but our working hypothesis is that they are not mutually exclusive and that they all contribute to the process. 39 We are currently exploring this issue of NIr mechanisms in other studies.…”
Section: Neuroprotection Of Dopaminergic Cells In the Snc Via Nir Aftmentioning
confidence: 99%